Morchella importuna Flavones Improve Intestinal Integrity in Dextran Sulfate Sodium-Challenged Mice - Xu, Yingyin; Xie, Liyuan; Tang, Jie; He, Xiaolan; Zhang, Zhiyuan; Chen, Ying; Zhou, Jie; Gan, Bingcheng; Peng, Weihong (Frontiers in Microbiology, 2021)
Morchella importuna, as an edible fungus, has various health benefits. However, the ef-fects of M. importuna on intestinal health are rarely investigated. Hence, this study aims to as-certain the influences of flavones from the fruiting bodies of M. importuna (hereinafter abbreviated as MIF) on dextran sulphate sodium (DSS)-induced damage to intestinal epithelial barrier in C57BL/6J mice. In this study (14-day), one hundred and forty-four C57BL/6J mice were divided into four groups: (1) Control; (2) DSS treatment; (3) DSS treatment + 100 mg/kg MIF (LMIF); (4) DSS treatment + 200 mg/kg MIF (HMIF). On days 8−14, mice in the challenged groups were challenged with 3.5% DSS, while the control group received an equal volume of normal saline. Then, serum and intestinal samples were obtained from all mice. The results showed that MIF ingestion enhanced intestinal integrity in DSS-challenged mice, as evinced by the elevated (P < 0.05) abundances of occludin, claudin-1 and zonula occludens-1 proteins. Meanwhile, MIF ingestion reduced (P < 0.05) the colonic IL-1β, TNF-α and IFN-γ concentrations and increased the superoxide dismutase and catalase activities and Shannon and Simpson indices in DSS-challenged mice. Moreover, MIF ingestion reduced (P < 0.05) the protein abundance of phospho-nuclear factor-κB (NF-κB) and increased the protein abundance of phospho-nuclear factor E2-related factor 2 (Nrf2) in DSS-challenged mice. Taken together, MIF protects against intestinal barrier injury in C57BL/6J mice via a mechanism that involves inhibiting NF-κB activation and promoting Nrf2 activation, as well as regulating intestinal microbiota.